Examining the Impact of Early Childhood School Investments on Neighborhood Crime. (29th July 2017) - Madero-Hernandez, Arelys; Deryol, Rustu; Ozer, M. Murat; Engel, Robin S.
Abstract : This study tested the hypothesis that investments in early childhood schools have short-term crime reducing effects in neighborhoods. Time series data from the city of Tulsa, Oklahoma, were analyzed to evaluate the effects of an early childhood school built in the neighborhood of Kendall-Whittier as part of a larger neighborhood revitalization plan, on violent and property crime. Results revealed that after controlling for city-wide crime trends and monthly fluctuations, violent crime declined significantly in Kendall-Whittier. Further analysis indicated that the possible crime-reducing effects of school investments on violent crime spread beyond Kendall-Whittier, and no displacement was found. The results for property crime were mixed. The study demonstrates the use of clustering analysis, a useful tool in neighborhood-level research to identify comparison neighborhoods. The findings shed light on the possibility that investments in early childhood schools can yield results in a shorter term than anticipated, making them a desirable component of urban revitalization.